Analisis Metode Capital Asset Pricing and Arbitrage Pricing Theory terhadap Investasi Saham - Selfiana Dewi; Cut Mutia; T. Aris Nouval; Muammar Khaddafi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to compare the effectiveness of the Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) in predicting stock returns through a literature review of 30 relevant studies. The findings show that CAPM, which relies solely on market risk, is more frequently proven accurate (18 studies) compared to APT (6 studies), while the remaining studies found no significant difference. Financial behavior also plays an important role in enhancing the accuracy of both models. Overall, CAPM is more effective in stable market conditions, while APT is more suitable in complex economic environments. Model selection should be based on market conditions and investor needs.